Staged Conservative Treatment of a Large Mandibular Odontogenic Cystic Lesion with Long-Term Follow-Up: A Case Report - Honório, Sérgio; da Silva, Tais Alves (Brazilian Journal of Case Reports, 2026)
Large mandibular odontogenic cystic lesions represent a clinical challenge due to their potential for bone destruction, pathological fracture, and involvement of vital structures such as the inferior alveolar nerve. The purpose of this case report was to describe the staged management of a large mandibular odontogenic cystic lesion and to evaluate its clinical outcome. A 54-year-old female patient presented with a large unilocular mandibular cystic lesion incidentally detected on routine radiographic examination. Initial diagnostic investigation included aspiration and cytopathological evaluation. A conservative approach was initially performed using cystic decompression with a Penrose drain, maintained and periodically replaced over 12 months. Serial radiographic examinations were used to monitor lesion reduction and bone regeneration. Following significant reduction, surgical enucleation and curettage of the residual cystic capsule were performed. Progressive reduction in cyst size and bone regeneration was observed during the decompression phase. The subsequent surgical procedure was performed safely with preservation of surrounding anatomical structures. Postoperative follow-up showed uneventful healing, maintenance of neurosensory function, satisfactory bone regeneration, and no evidence of recurrence. Staged management combining prolonged decompression and delayed enucleation is an effective and safe approach for large mandibular odontogenic cystic lesions. This strategy reduces surgical morbidity, preserves anatomical structures, and provides predictable clinical outcomes, supporting its use in similar clinical situations.